miR-342 suppresses the proliferation and invasion of acute myeloid leukemia by targeting Naa10p - Haiyan Wang; Heng He; Chunyan Yang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Accumulating studies showed that microRNAs are maintaining a variety of important biological processes but the underlying mechanism in proliferation and tumourigenicity is unclear. In this study we show that miR-342 expression in bone marrow and patients’ sera of childhood acute myeloid leukemia (AML) was both significantly higher than those in the corresponding normal controls. Functional assays demonstrated that forced expression of miR-342 significantly suppresses AML cell proliferation and G1/S transition of leukemia cells. Mechanistically, bioinformatics prediction and luciferase reporter assay identified N-a-acetyltransferase 10 protein (Naa10p) as a direct molecular target of miR-342, Naa10p siRNA significantly repressed cell proliferation and increased cell apoptosis. In conclusion, our study confirmed that miR-342/Naa10p plays key roles in AML progression, providing insights into underlying mechanisms of AML pathogenesis and also a potential therapeutic target for this malignancy.